2021
DOI: 10.3390/diagnostics11030497
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30-Day and 180-Day Mortality in Elderly Proximal Hip Fracture Patients: Evaluation of 4 Risk Prediction Scores at a Level I Trauma Center

Abstract: This study evaluated the use of risk prediction models in estimating short- and mid-term mortality following proximal hip fracture in an elderly Austrian population. Data from 1101 patients who sustained a proximal hip fracture were retrospectively analyzed and applied to four models of interest: Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (POSSUM), Charlson Comorbidity Index, Portsmouth-POSSUM and the American College of Surgeons National Surgical Quality Improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…30-day mortality in our cohort was 7.7% (2321 patients) and was comparable to other studies. Nia et al 8 report a 30-day mortality of 6.1% in their cohort of 1101 hip fractures, Van Rijckevorsel et al 16 7.9% in 2458, Karres et al 5 8.2% in 1050, Haugan et al 17 7.5% in 3651, Maxwell et al 6 7.8 in 4967, and in 2020, the Royal College of Physicians National Hip Fracture Database reported a 6.5% mortality in 67,302 patients. 18 Only 2 predictive models of 30-day mortality have been specifically developed for hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30-day mortality in our cohort was 7.7% (2321 patients) and was comparable to other studies. Nia et al 8 report a 30-day mortality of 6.1% in their cohort of 1101 hip fractures, Van Rijckevorsel et al 16 7.9% in 2458, Karres et al 5 8.2% in 1050, Haugan et al 17 7.5% in 3651, Maxwell et al 6 7.8 in 4967, and in 2020, the Royal College of Physicians National Hip Fracture Database reported a 6.5% mortality in 67,302 patients. 18 Only 2 predictive models of 30-day mortality have been specifically developed for hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, no analysis of its predictive performance is reported, nor has it been validated in consequent studies. 8 RNFC model include 4 variables (age, gender, ASA score, pre-fracture mobility) that are also use in this model. The other 3 variables (dementia, pathological fracture, and osteoprotective medication) are not included in this model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the NHFS was the most promising models with reasonable discrimination and extensive validation for predicting 30-day mortality in hip fracture surgery. Nia et al 54 compared four risk prediction scores for 30-day and 180-day mortality in elderly proximal hip fracture patients, including the POSSUM, the Portsmouth-POSSUM (P-POSSUM), the CCI and National Surgical Quality Improvement Programme (NSQIP) Risk Score. They found that ACS-NSQIP had the highest predictive value for both 30-day and 180-day mortality in elderly proximal hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%